Planejamento de ações manipulativas de crianças com baixa visão e visão normal - MEDEIROS, Jéssica Cristina (2014)
Planning a motor action involves the choice of the most efficient movement strategy considering the final objective of this action, a concept presented in the literature as end-state comfort effect. With the aim of studying the planning of motor actions of typical children and with low vision two studies were carried out. The first study aimed at making a systematic review of the planning of motor actions of typical and atypical children. From a search on the main databases it was found ten studies with typical children (nine months to 12 years old), and five with atypical children (cerebral palsy, autism and developmental coordination disorders) between 3 and 14 years old. In typical children these studies report that the ability of motor planning is totally developed between nine to ten years old, however in atypical children the results are not conclusive yet. The aim of the second study was to verify the influence of visual impairment in the ability of planning of motor actions in children with low vision from seven to twelve years old. 29 children with low vision and 75 children with normal vision participated in this study. Children were requested to perform a manual task to fit a wooden bar. It was analyzed the percentage of correct responses consistent to end-state comfort. There were no significant differences between the groups for this task for all ages; and the capacity of planning in both groups was not entirely developed until twelve years old. It was concluded that, for being the first study with Brazilian children with low vision diagnosis, the results could be considered positive, whereas there was no significant difference in the capacity of motor planning of these children when compared to children with normal vision. However, observing the motor planning of these children it can be noticed lower performance than other children’s in the literature, at the same age but from different nationalities. Based on this information, it is highlighted the importance of doing more studies with Brazilian children from seven years old and with atypical children, mainly those with low vision.